Characteristics and outcomes of hip fractures in lower limb amputees. Issue 4 (April 2021) - Haleem, S.; Yousaf, S.; Hamid, T.; Nagappa, S.; Parker, M.J.
Highlights: Lower limb amputees, regardless of age are at an increased risk of developing fragility fractures of the neck of femur. We compared patients with hip fractures and previous lower limb amputation with a cohort of standard hip fracture patients. Results showed that seventy percent of amputees returned to their previous level of mobility and prior residence. Mortality in the amputee group was higher but pain and mobility were comparable in both groups. Our study reveals that management of hip fractures in amputees can have comparable results (pain scores, mobility index, length of stay and return to previous residence) to a standard hip fracture cohort. Abstract: Introduction: Lower limb amputees, regardless of age are at an increased risk of developing fragility fractures of the neck of femur. The characteristics and outcomes of the fractures of the neck of femur in lower limb amputees have not been studied in detail. Methods: We undertook a retrospective review of a prospectively collected single centre and single surgeon database between March 1996 and January 2017, using a standard proforma to identify patients who required surgical intervention for fracture neck of femur and had sustained a previous lower limb amputation and compared them with a cohort of standard hip fracture patients. Results: Twenty-seven patients, sustaining 28 fractures of the neck of femurs were identified of which 16 were females with mean age of 78 years (50-89). Nineteen fractures were sustained on the ipsilateral side of the amputation. Results showed that seventy percent of amputees returned to their previous level of mobility and prior residence. Mortality in this group is higher as compared to a standard hip fracture patient but pain and mobility were comparable in both groups. Discussion: The incidence of both hip fractures and amputations in increasing worldwide but no study has compared outcomes of hip fractures in amputees and compared them to a standard hip fracture patient. Amputees exhibit reduced bone density both at the hip and stump end which increases risk for osteoporosis and fragility fractures in the hip. The management of our patients followed orthopaedic principles, well established surgical interventions and rehabilitation. Conclusion: This study reveals that hip fractures in amputees can have comparable results to a standard hip fracture cohort if preoperative optimisation, planning and postoperative rehabilitation is carried out.